Public Health Nurses' Experiences during the H1N1/09 Response - Devereaux, Alana (Université d'Ottawa / University of Ottawa, 2016)
The H1N1/09 (sub-type A) virus was declared to be a pandemic influenza on June 11th, 2009. In response, Canadian public health agencies planned mass vaccination clinics to protect the public. However, little information existed to aid in the planning of mass vaccination clinics, as they had not been used in previous pandemic flu outbreaks. This was further complicated by fear of a limited vaccine supply and nurse shortages. Public health nurses (PHNs), as the largest group of public health professionals were pivotal in implementing the mass vaccination clinics. Yet, the available evidence indicated that PHNs involvement in H1N1/09 response planning was limited and their experiences on the frontline in the mass vaccination clinics were not well understood. The purpose of this study was to give PHNs’ a voice to describe their experiences in the H1N1/09 mass vaccination clinics. A framework based on Foucault’s concepts of knowledge, power, and resistance was developed as the theoretical lens to guide the research. Using an interpretive descriptive methodology, a purposeful sample of 23 PHNs (16 front-line immunizers, seven clinic supervisors) participated in semi-structured interviews. Four pandemic planning documents containing policies in place during the pandemic outbreak were also reviewed to provide context to participants’ experiences. Interpretive descriptive analysis was used to analyze the interviews and pandemic documents. Guba and Lincoln’s (1994) trustworthiness framework was implemented to evaluate the rigour of the study’s findings. Two overall core themes emerged to describe participants’ experiences. The core theme ‘the necessity of knowledge’, illustrated participants’ feelings of unpreparedness entering into the H1N1/09 clinics. Limited notice of the pandemic response, uncertainties regarding the clinics’ anticipated timeframe, and a lack of knowledge on vaccination and clinic management, contributed to a loss of power in the participants’ role. In the second core theme ‘essential supports in protecting the population’, many perceived a lack of agency support when they tried to exercise power in their clinical practice. Although participants did not refuse to immunize in, or supervise, the mass vaccination clinics, participants at times did display subtle resistance. Insights gained from participants’ experiences have implications in terms of public health nursing administration, practice, research, and education. A key recommendation is to involve PHNs in future pandemic planning to optimize mass vaccination clinics’ operations. If this cannot happen, PHNs should at least be informed of the disciplinary discourse utilized to guide clinical decisions. This will help nurses be supported in their own pandemic roles and contribute to the provision of quality population care.
Keywords: Public Health; Interpretive Description; Mass vaccinations; nursing; Pandemic H1N1/09; influenza